NEW FLARE STARS AND THE SAN LUIS POTOSIECTRUM RATE OF VARIATION RELATION - HARO, G; CHAVIRA, E (UNAM, Observatorio Astronómico Nacional, CD MEXICO, DF, MEX, 1956)
In this study we confirm that whenever there is a group of T Tauri stars, there is the possibility of finding, associated to them, rapid variables. We have thus found 7 new variables of the UV Ceti Type in the Taurus dark region. From the new data we can
BOL OBS TONAN TACUB
Keywords: NEW, FLARE, STARS, SPECTRUM, RATE, VARIATION RELATION; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS